Kewenangan Electoral Management Bodies dalam Menangani Tindak Pidana Pemilu dalam Perspektif Perbandingan - Santoso, Topo (UI Scholars Hub, 2009)
This article discusses the role and power of the electoral management body regarding settlement of election irregularities. Every jurisdiction has its own approach and mechanism to prevent, oversee, and punish the perpetrator of the election irregularities and election offences. This article overview the differences of the Electoral Body’s role and power in the election offences settlement process. The conclusion is that, the role and power of the Philippine’s Electoral Commission (Comelec) is the widest and strongest compare to three other countries (Indonesia, Malaysia, Singapore). In order to have more effective settlement process, this article comes to the conclusion that the KPU needs to be provided with the role and power to supervise and initial handling of certain irregularities by means of special division, namely supervisory and law enforcement division.